Phasic abnormalities of left ventricular emptying in coronary artery disease. - Walton, S (1981)
Seventy subjects with suspected coronary artery disease were studied by radionuclide angiocardiography. Delayed or paradoxically emptying regions of the left ventricle were detected by a relatively new nuclear technique--phase imaging. The results were assessed in the light of cardiac catheterisation findings. Compared with 19 normals, regions with abnormally high phase (and therefore late emptying) were found in 42 of 61 subjects with coronary disease. High phase values were associated with total occlusion of a major coronary artery, low ejection fraction, and extensive wall motion abnormalities. The phase image greatly facilitated the calculation of contractile segment ejection fraction in 14 cases of left ventricular aneurysm. In three of these postoperative left ventricular ejection fraction agreed closely with preoperative contractile segment ejection fraction and there was a distinct improvement in the phase image after aneurysmectomy.